Stres pada Siswa Madrasyah Aliya “B” di Mariana Kabupaten Banyuasin - Santi Rosalina; Heriziana. Hz (Universitas Muhammadiyah Manado, 2024)
Basic Health Research Data (Riskesdas) in 2018, the prevalence of adolescents aged >15 years who experience emotional disorders in the form of stress, depression and anxiety disorders reached 9.8% (Ministry of Health of the Republic of Indonesia, 2018) . The large number of academic assignments makes students have to work on these assignments until late at night and become tired and sleepy in class. This causes students to be lazy to study and less able to concentrate on lessons in class. Students also often feel anxious during exams and are afraid of lowering their grades . This study aims to obtain a description of academic stress and the characteristics of students at Madrasah Aliyah